2020
DOI: 10.7759/cureus.10483
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Liver Disease and the Risk of Osteoporotic Fractures: A Meta-Analysis

Abstract: Introduction Chronic liver disease (CLD) causes more than 1 million deaths every year and remains a pandemic in the last decade affecting more than 600,000 patients in the United States. Previous studies found patients with CLD had increased risk of osteoporosis, so fractures were inferred to be complications of this condition. The aim of this meta-analysis is to summarize the best evidence that correlates CLD patients and the risk to develop osteoporotic fractures versus control patients without CLD. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…There are many reasons why metabolic changes that are caused by liver cirrhosis could have an impact on the early stages of osseointegration. Cirrhosis is a risk factor for osteoporotic fractures suggesting an effect of cirrhosis on bone metabolism that may extend toward bone regeneration (Handzlik‐Orlik et al., 2016 ; Hidalgo et al., 2020 ; Luxon, 2011 ). Also, the frequency of oral mucosal lesions in patients with chronic liver failure was higher compared with the control group (Zahed et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many reasons why metabolic changes that are caused by liver cirrhosis could have an impact on the early stages of osseointegration. Cirrhosis is a risk factor for osteoporotic fractures suggesting an effect of cirrhosis on bone metabolism that may extend toward bone regeneration (Handzlik‐Orlik et al., 2016 ; Hidalgo et al., 2020 ; Luxon, 2011 ). Also, the frequency of oral mucosal lesions in patients with chronic liver failure was higher compared with the control group (Zahed et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of cirrhosis in industrialized countries is estimated at 0.3% (Scaglione et al., 2015 ). Regardless of the etiology, cirrhosis doubles the risk of pathological fractures (Handzlik‐Orlik et al., 2016 ; Hidalgo et al., 2020 ; Luxon, 2011 ). Moreover, cirrhotic patients with fractures had significantly higher mortality and hospitalization rate than the regular population (Mavilia et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic osteodystrophy is common in patients with advanced cirrhosis (4)(5)(6). Decline in bone mineral density (BMD) is invariably associated with poor quality of life and increased risk of fractures in this population (7). However, unlike muscle and fat mass, impact of BMD or changes in it on liver related outcomes is poorly understood at present.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of six case–control studies demonstrated that the prevalence of osteoporosis in patients with liver cirrhosis (LC) was significantly higher than that in healthy individuals [34.7% vs. 12.8%; odds ratio (OR) = 2.52] [ 5 ]. Another meta-analysis of seven studies revealed a significant association between CLD and the risk of osteoporotic fractures, with a pooled OR of 2.13 [ 8 ]. Specifically, vertebral fractures are more common in patients with CLD.…”
Section: Introductionmentioning
confidence: 99%
“…Bone health is a global concern, because bone disorders are related to poor health-related quality of life, disability, and prognosis [1]. Osteoporosis, a metabolic bone disease, and consequent fragility fractures are common extrahepatic complications in patients with chronic liver disease (CLD) [2][3][4][5][6][7][8][9]. A meta-analysis of six case-control studies demonstrated that the prevalence of osteoporosis in patients with liver cirrhosis (LC) was significantly higher than that in healthy individuals [34.7% vs. 12.8%; odds ratio (OR) = 2.52] [5].…”
Section: Introductionmentioning
confidence: 99%